Lipid profiling of the filarial nematodes Onchocerca volvulus, Onchocerca ochengi and Litomosoides sigmodontis reveals the accumulation of nematode-specific ether phospholipids in the host. Issue 14 (December 2017) - Wewer, Vera; Makepeace, Benjamin L.; Tanya, Vincent N.; Peisker, Helga; Pfarr, Kenneth; Hoerauf, Achim; Dörmann, Peter
Graphical abstract: Highlights: Onchocerciasis is an infectious disease caused by filarial nematodes. Three different filarial nematodes infecting cattle, humans and jirds were studied. Phospholipids in nematodes and hosts were determined by mass spectrometry. Filaria-specific ether phosphatidylethanolamine (PE) lipids accumulate in the host. These ether PE lipids could serve as potential biomarkers for onchocerciasis. Abstract: Onchocerciasis, a neglected tropical disease prevalent in western and central Africa, is a major health problem and has been targeted for elimination. The causative agent for this disease is the human parasite Onchocerca volvulus . Onchocerca ochengi and Litomosoides sigmodontis, infectious agents of cattle and rodents, respectively, serve as model organisms to study filarial nematode infections. Biomarkers to determine infection without the use of painful skin biopsies and microscopic identification of larval worms are needed and their discovery is facilitated by an improved knowledge of parasite-specific metabolites. In addition to proteins and nucleic acids, lipids may be suitable candidates for filarial biomarkers that are currently underexplored. To fill this gap, we present the phospholipid profile of the filarial nematodes O. ochengi, O. volvulus and L. sigmodontis. Direct infusion quadrupole time-of-flight (Q-TOF) mass spectrometry was employed to analyze the composition of phospholipids and their molecular species in the three nematode species. Analysis of the phospholipid profiles of plasma or serum of uninfected and infected hosts showed that nematode-specific phospholipids were below detection limits. However, several phospholipids, in particular ether lipids of phosphatidylethanolamine (PE), were abundant in O. ochengi worms and in bovine nodule fluid, suggesting that these phospholipids might be released from O. ochengi into the host, and could serve as potential biomarkers.